Search for first-generation scalar leptoquarks in pp̄ collisions at √s = 1.96 TeV - Abazov, V. M.; Abbott, B.; Abolins, M.; Acharya, B. S.; Adams, M.; Adams, T.; Agelou, M.; Agram, J. L.; Ahn, S. H.; Ahsan, M.; Alexeev, G. D.; Alkhazov, G.; et al. (American Physical Society (APS), 2005)
We report on a search for pair production of first-generation scalar leptoquarks (LQ) in pp̄ collisions at √s = 1.96 TeV using an integrated luminosity of 252 pb-1 collected at the Fermilab Tevatron collider by the D0 detector. We observe no evidence for LQ production in the topologies arising from LQLQ → eqeq and LQLQ → eqvq, and derive 95% C.L. lower limits on the LQ mass as a function of β, where β is the branching fraction for LQ → eq. The limits are 241 and 218 GeV/c 2 for β = 1 and 0.5, respectively. These results are combined with those obtained by D0 at √s = 1.8 TeV, which increases these LQ mass limits to 256 and 234 GeV/c2. © 2005 The American Physical Society.